The Banks set and the bipartisan set may be disjoint - Felix Brandt; Florian Grundbacher (Social Choice and Welfare, 2025)
Tournament solutions play an important role within social choice theory and the mathematical social sciences at large. We construct a tournament of order 36 that can be partitioned into the Banks set and the bipartisan set. As a consequence, the Banks set, as well as its refinements, such as the minimal extending set and the tournament equilibrium set, can be disjoint from the bipartisan set.
Keywords: 330